Compact substrate integrated waveguide filter using dual‐plane resonant cells. Issue 1 (January 2016) - Liu, Jun‐Ping; Lv, Zhi‐Qing; An, Xiang
ABSTRACT: A dual‐plane resonant cell wideband bandpass filter is proposed and designed on substrate integrated waveguide (SIW) cavities using U‐shape slots and H‐shape fractal defected ground structure (DGS). The U‐shape slots etched on the top meta layer of the SIW cavity are used to constitute a multiple‐mode resonator and the H‐shape fractal DGS etched on the bottom metal layer can greatly improve the filter performance while keeping the overall size of the filter circuit to be much compact. The proposed filter can lead to a size reduction of approximately one‐third compared with the traditional SIW filters only using U‐shape slots on the top metal plate of the SIW cavity. The filter has been fabricated and experimentally measured. The measured data are in good agreement with the simulated results. The measured 3 dB bandwidth is from 7.15 to 11.25 GHz, representing a fractional bandwidth of 44.6% at a center frequency of 9.2 GHz. Within the passband, the measured return loss performance is quite good (below −22dB), and the insertion loss is measured to be 1.05 dB, including the loss from two SMA connectors. © 2016 Wiley Periodicals, Inc. Microwave Opt Technol Lett 58:111–114, 2016